2019
DOI: 10.3390/cells8090990
|View full text |Cite
|
Sign up to set email alerts
|

Intraarticular Ligament Degeneration Is Interrelated with Cartilage and Bone Destruction in Osteoarthritis

Abstract: Osteoarthritis (OA) induces inflammation and degeneration of all joint components including cartilage, joint capsule, bone and bone marrow, and ligaments. Particularly intraarticular ligaments, which connect the articulating bones such as the anterior cruciate ligament (ACL) and meniscotibial ligaments, fixing the fibrocartilaginous menisci to the tibial bone, are prone to the inflamed joint milieu in OA. However, the pathogenesis of ligament degeneration on the cellular level, most likely triggered by OA asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 127 publications
(199 reference statements)
1
42
0
Order By: Relevance
“…The parallel cell arrangement and longitudinal orientation according to the thread direction observed in the present study by SEM and live/dead staining is comparable to cell alignment in the native ACL [47] and was observed in another scaffold type consisting of braided nanofibers [48].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The parallel cell arrangement and longitudinal orientation according to the thread direction observed in the present study by SEM and live/dead staining is comparable to cell alignment in the native ACL [47] and was observed in another scaffold type consisting of braided nanofibers [48].…”
Section: Discussionsupporting
confidence: 84%
“…Cells were detached with 0.05% typsin/0.02% EDTA (Merck KGaA, Darmstadt, Germany) and counted with a hemocytometer. Spheroids were achieved by using the hanging drop method as described previously [47] with a cell number of 2.5 × 10 4 per spheroid. After two days of spheroid formation at 37 • C and 5% CO 2 , they were carefully harvested.…”
Section: Spheroid Based Statical Scaffold Colonizationmentioning
confidence: 99%
“…A previous study revealed that the degeneration of the intraarticular ligament was highly associated with cartilage and bone damage during the OA process. 151 Destruction of ligament integrity, such as the cruciate ligament, seriously decreased joint stability and promoted the development of knee OA, indicating an important role of the ligament in OA disease. [152][153][154] Zhao et al isolated exosomes from periodontal ligament stem cells using an ultracentrifugation method and identified their exosomal characteristics by TEM, western blot and nanosight tracing analysis.…”
Section: Exosomes In Oamentioning
confidence: 99%
“…During the development of OA, degeneration of all joint constituents including cartilage, synovial membrane, bone, bone marrow and ligaments occurs [36,43]. The biological imbalance and the mechanical stress lead to a pathological situation with altered chondrocyte behavior releasing inflammatory mediators and ECM destruction enzymes [35,[44][45][46].…”
Section: Osteoarthritismentioning
confidence: 99%